The Influence of Work Motivation, Work-Life Balance, Career Development, and Job Satisfaction on Employee Performance in The Ministry of MSMEs - Gunawan; Sri Langgeng Ratnasari; Amir Tengku Ramly (Universitas Pamulang, 2026)
This study aims to analyze the influence of work motivation, work-life balance, career development, and job satisfaction on employee performance at the Ministry of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative approach and multiple linear regression analysis on primary data, the results show that work–life balance and job satisfaction have a positive and significant effect on employee performance. Simultaneously, all four variables significantly affect employee performance. The coefficient of determination indicates that 59.5% of employee performance is explained by the four variables. These findings suggest that in the public sector environment of the Ministry of MSMEs, organizational interventions should psychological well-being and work-life harmony over traditional motivational triggers or career-pathing to yield performance gains. This study contributes to public sector management literature by identifying factors in influencing performance amidst bureaucratic constraints.